Overview of Huntington's Disease Models: Neuropathological, Molecular, and Behavioral Differences. Issue 1 (26th April 2018) - Rangel‐Barajas, Claudia; Rebec, George V.
Abstract: Transgenic mouse models of Huntington's disease (HD), a neurodegenerative condition caused by a single gene mutation, have been transformative in their ability to reveal the molecular processes and pathophysiological mechanisms underlying the HD behavioral phenotype. Three model categories have been generated depending on the genetic context in which the mutation is expressed: truncated, full‐length, and knock‐in. No single model, however, broadly replicates the behavioral symptoms and massive neuronal loss that occur in human patients. The disparity between model and patient requires careful consideration of what each model has to offer when testing potential treatments. Although the translation of animal data to the clinic has been limited, each model can make unique contributions toward an improved understanding of the neurobehavioral underpinnings of HD. Thus, conclusions based on data obtained from more than one model are likely to have the most success in the search for new treatment targets. © 2018 by John Wiley & Sons, Inc.